Case report: Application of morphology in the diagnosis of siderosis in a patient with tuberculosis infection - Zhou, Yuli; Wang, Ying; Liu, Wenbing; Wang, Haibin; He, Daqiang; Jin, Juan; Li, Qiaoyun; Li, Junying; Chen, Qiong; Ruan, Senlin; Wu, Shenghai; Tang, Jiyu (Frontiers in Oncology, 2023)
A 49-year-old male who had been working in welding for more than 30 years was admitted to the hospital for a medical checkup that revealed a lung shadow without specific symptoms such as coughing and sputum. Imaging studies showed diffuse ground-glass changes in both lungs, wall cavities with wall nodules, multiple peripheral nodules, and some nodules with calcification. The patient has been engaged in welding work for more than 30 years and exposed to iron dust. Lung tissue biopsy, routine morphological and pathological fluid basis examination of alveolar lavage fluid, can be considered as pulmonary iron particles, which can be regarded as iron dust lung. Acid-fast bacilli were detected in both fibrobronchoscopic brush extract and alveolar lavage fluid acid-fast staining. As the pathological examination revealed granulomatous inflammation showed caseation necrosis, the patient was judged to have concomitant pulmonary TB. . After the diagnosis was made, the patient was no longer exposed to dust and was treated with appropriate anti- tuberculosis (TB) therapy. Lung lesions caused by welding have been reported, but the simultaneous finding of siderosis with pulmonary TB is specific to the case presented here. By describing the imaging features, combining different staining methods of alveolar lavage fluid and pathological examination of lung tissue, we showed various morphological manifestations of this case, aiming at improving the morphological diagnosis level of laboratory physicians and enabling patients to be diagnosed and treated early.